Host species-specific interactions of protein kinase R and poxvirus pseudosubstrate inhibitors - Peng, Chen (Kansas State University, 2016)
Poxviruses are large double-stranded DNA viruses that collectively exhibit a broad host range. Whereas many members of the poxvirus family are capable of infecting various host species, others are restricted to only one or a very limited numbers of species, such as variola virus, which is the causative agent of smallpox and is restricted to humans. Since the entry of poxviruses is not dependent upon any specific receptors, the cell tropism is therefore fully determined by the virus’ ability to manipulate the cellular signaling networks that are responsible for antagonizing viral infections. Double-stranded RNA (dsRNA)-dependent protein kinase (PKR) is a unique antiviral protein found in most vertebrates, which serves both as a virus sensor by detecting the presence of dsRNA and an antiviral effector by suppressing cap-dependent translation during virus infection. Many viruses, including poxviruses, have therefore evolved genes that encode for PKR inhibitors, such as vaccinia virus K3L, which shows sequence homology to the N-terminal region of the eukaryotic translation initiation factor 2α (eIF2α), the substrate of PKR. K3L is able to inhibit PKR-mediated eIF2α phosphorylation in vitro and in vivo. Because K3L was shown to be indispensable for virus replication in Syrian hamster cells but not in human cells, it was categorized as a host range factor. However, the molecular basis for K3L’s host range function is not fully understood. We examined the interactions of poxvirus K3L orthologs, especially vaccinia virus K3L and M156R, the K3L ortholog in the rabbit-specific myxoma virus, and PKR from a variety of host species in multiple assays, and found that K3L and M156R inhibit PKR in a species-specific manner, which likely contributes to the cell tropism and host range for both viruses. Inactivation of M156R or K3L led to virus attenuation in cells, which could be rescued by ectopic expression of viral PKR inhibitors. We also identified the helix αG region as the main molecular determinant for PKR’s sensitivity to inhibition by K3L orthologs. In conclusion, the research summarized here indicates that the interactions of PKR and poxvirus pseudosubstrate inhibitors play important roles in virus host range and virulence.
Keywords: Poxvirus; Protein kinase R; Virus-host co-evolution